2021
DOI: 10.1039/d0ra10605d
|View full text |Cite
|
Sign up to set email alerts
|

Meso-functionalization of calix[4]arene with 1,3,7-triazapyrene in the design of novel fluorophores with the dual target detection of Al3+ and Fe3+ cations

Abstract: Novel bifunctional fluorophores with the dual target detection of Al3+ and Fe3+ cations were synthesized in yields up to 70% via bridge-functionalization of calix[4]arenes with the 1,3,7-triazapyrene scaffold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Additionally, cellular non-toxicity of 11 was evaluated by an MTT assay, permitting its applications to be extended to the biology field. Moseev et al reported mesofunctionalization of calix [4]arene 12 with 1,3,7-triazapyrene for the dual target detection of Al 3+ and Fe 3+ cations 40 (Fig. 6).…”
Section: Detection Of Al 3+mentioning
confidence: 99%
“…Additionally, cellular non-toxicity of 11 was evaluated by an MTT assay, permitting its applications to be extended to the biology field. Moseev et al reported mesofunctionalization of calix [4]arene 12 with 1,3,7-triazapyrene for the dual target detection of Al 3+ and Fe 3+ cations 40 (Fig. 6).…”
Section: Detection Of Al 3+mentioning
confidence: 99%
“…In 2019, the Rao group prepared a calix[4]arene‐coupled cyclic compound by connecting nitrobenzimidazole (NBD) to the lower rim of calix[4]arene for recognizing trivalent metal ions (Cr 3+ , Fe 3+ , Al 3+ ) [8] . Most recently, the Chupakhin group designed a 1,3,7‐triazaperylene calix[4]arene for detecting Al 3+ and Fe 2+ [9] …”
Section: Introductionmentioning
confidence: 99%
“…[8] Most recently, the Chupakhin group designed a 1,3,7-triazaperylene calix [4]arene for detecting Al 3 + and Fe 2 + . [9] In the past decade, our group has developed a series of upper and lower-rim functionalized calix [4]arenes to achieve various organic catalysis and molecular recognition. [10] Notably, we have found that upper-rim functionalized calix [4]arenes have distinct advantages over the common lower-rim functionalized calixarenes in their ability to fully utilize the calix [4]arene cavity structure and cation ••• π interactions to enhance recognition abilities.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive development of transition‐metal‐free CH‐functionalization reactions started only in the decade of 1960–1970 and first review article was published in 1976 [10] . Now transition‐metal‐free C−H functionalization has become an obvious choice for the direct functionalization of (het)arenes, [11–16] including macrocycles [17–20] …”
Section: Introductionmentioning
confidence: 99%
“…[10] Now transition-metal-free CÀ H functionalization has become an obvious choice for the direct functionalization of (het)arenes, [11][12][13][14][15][16] including macrocycles. [17][18][19][20] The early and pioneering transition-metal-catalyzed CÀ H functionalization/activation reaction in…”
Section: Introductionmentioning
confidence: 99%